A Review of Resistance of Fishing Boat Skipjack Pole and Line. - Wolter Robeth Hetharia (Fakultas Teknik UPN Veteran Jakarta, 2026)
Skipjack Pole and Line Fishing Boat are designed and constructed to catch big pelagic fishes like tuna (Thunnus spp) and skipjack tuna (Katsuwonus Pelamis). Previous study executed by the authors found that there is no ship complete database and specific resistance method to find the resistance parameter at early design phase. The purpose of this study is to find a proper existing method of ship resistance to be applied for this kind of ship. The study began with collecting the existing ship database then developed ship geometry in Maxsuf Software in order to develop ship parameters including ship model for model test. Model test procedure was executing based on standard procedure of testing model in towing tank. The result of model test was compared to some possible methods for fishing ship resistance such as Holtrop, Guldhammer, and Yamagata Methods. Results of model test was extrapolated to full-scale ship. All the resistance data of approach methods were compared to those of model test. It was found from the study that for all range of ship speed the method Guldhammer was very close to the results of model test. Particularly at service speed around 9 to 11 knots the differences are 2% to 4%. It may be concluded from the study that Resistance Method of Guldhammer may be applied to estimate the resistance of Skipjack Pole and Line at early design phase